Resonances in Conductance Through Tunable Attractors. Issue 1 (1998) - Joe, Yong S.; Cosby, Ronald M.
Abstract : We present the effects of resonant tunneling through doubly-coupled attractors in series in a quantum nanosystem. It is found that multiple split-tunneling peaks arise from resonant tunneling through multiple nondegenerate quasi-bound-states of the coupled attractors. We show that the tunability of coupling is achieved by modulating the strength of the attractor for a fixed separation length between the attractors, and by adjusting the geometrical separation length for a fixed intervening barrier strength.